Prevalence of undernutrition and associated factors among adolescent pregnant women in Dolo-Ado town, Somali region, Ethiopia - Abdirahman Ahmed; Abdulkarim Mohammed; Mahamed Dol Ateye; Saleha Abdusamed (BMC Pregnancy and Childbirth)
Abstract Background Maternal malnutrition, particularly among adolescent pregnant women, is a significant public health issue globally, with far-reaching consequences for both maternal and fetal health. It increases the risk of complications such as stillbirth, low birth weight,preterm birth, uterine bleeding, and other pregnancy-related issues. Objective This study aimed to assess the prevalence of undernutrition and associated factors among adolescent pregnant women (aged < 20 years) in the Dolo-Ado town, Somali region, Ethiopia. Methods and materials A cross-sectional study was conducted from January 1–30, 2022, involving 380 pregnant adolescents randomly selected from the Dolo-Ado town. A structured, pretested questionnaire was used to gather data on socio-demographics, maternal nutrition, and obstetric characteristics. Nutritional status was assessed using mid-upper arm circumference (MUAC), with undernutrition defined as MUAC ≤ 22 cm. Data were collected via home visits, and the accuracy of anthropometric measurements was standardized through training and pretesting. Descriptive statistics were used for data description, and binary logistic regression was performed to explore the associations between independent and dependent variables. Results A total of 380 pregnant adolescents participated, achieving a 100% response rate. The mean age of the participants was 17.7 (± 0.78) years. Approximately 32.1% of the participants experienced food insecurity, and only 3% met the minimum dietary diversity score. The prevalence of undernutrition was 21% (79/380), as indicated by a MUAC of < 22 cm. Conclusion The high prevalence of undernutrition among pregnant adolescent women in Dolo-Ado poses a significant public health concern. Key factors associated with undernutrition include maternal education [AOR] of 3.9; 95% Confidence Interval [CI]: 1.9–8.0), rural residence (AOR of 12; 95% CI: 3.5–42.9), low family income (AOR of 2.6; 95% CI: 1.2–5.4), food insecurity (AOR of 6.2; 95% CI: 2.8–13.9), iron-folic acid supplementation (AOR of 3.6; 95% CI: 1.7–7.5), and low dietary diversity intake (AOR of 13.1; 95% CI: 2.2–77.3). Therefore, targeted efforts to address family income, household food insecurity, dietary diversity, and access to iron-folic acid supplementation should be prioritized by both government and non-governmental organizations for pregnant adolescents.